Simeprevir plus sofosbuvir in patients with chronic hepatitis C virus genotype 1 infection and cirrhosis: A phase 3 study (OPTIMIST‐2). Issue 2 (19th February 2016) - Lawitz, Eric; Matusow, Gary; DeJesus, Edwin; Yoshida, Eric M.; Felizarta, Franco; Ghalib, Reem; Godofsky, Eliot; Herring, Robert W.; Poleynard, Gary; Sheikh, Aasim; Tobias, Hillel; Kugelmas, Marcelo; et al.
Abstract : Hepatitis C virus (HCV)–infected patients with cirrhosis are historically a difficult‐to‐treat population and are at risk of hepatic decompensation. In the phase 2 COSMOS study that evaluated simeprevir (HCV NS3/4A protease inhibitor) + sofosbuvir (HCV nucleotide analogue NS5B polymerase inhibitor) ± ribavirin for 12 or 24 weeks in HCV genotype (GT)1–infected patients, high rates of sustained virologic response 12 weeks after planned end of treatment (SVR12) were achieved, including in patients with cirrhosis (METAVIR score F4). This phase 3, open‐label, single‐arm study (OPTIMIST‐2 [NCT02114151]) evaluated the efficacy and safety of 12 weeks of simeprevir + sofosbuvir in HCV GT1–infected treatment‐naive or treatment‐experienced patients with cirrhosis. Patients (aged 18‐70 years) with chronic HCV GT1 infection and documented presence of cirrhosis received oral simeprevir 150 mg once daily + sofosbuvir 400 mg once daily for 12 weeks. The primary efficacy endpoint of the study was the proportion of patients achieving SVR12 versus a composite historical control (SVR12 rate of 70%). Safety and patient‐reported outcomes were assessed. Overall, 103 patients received treatment. SVR12 with simeprevir + sofosbuvir (83%, 95% confidence interval 76%‐91%) met the primary objective of superiority versus the historical control (70%). SVR12 rates for treatment‐naive and treatment‐experienced patients were 88% (44/50) and 79% (42/53), respectively. Adverse events occurred in 72 (70%) patients, with most (64%) being grade 1 or 2. Serious adverse events (none considered related to study treatment) occurred in five (5%) patients, and three (3%) patients discontinued all study treatment due to adverse events. Patient‐reported outcomes improved from baseline to follow‐up week 12. Conclusion: Simeprevir + sofosbuvir for 12 weeks achieved superiority in SVR12 rates versus the historical control in treatment‐naive and treatment‐experienced HCV GT1‐infected patients with cirrhosis and was generally safe and well tolerated. (Hepatology 2016;64:360‐369)